Effect of Novel All-in-One Root Canal Irrigants on Dislodgement Resistance of Epoxy Resin and Hydraulic Calcium Silicate Sealers: An Ex vivo Study - Kamath, Shreeraksha; Narkedamalli, Rajkumar; Shetty, Krishna Prasad; Ballal, Nidambur Vasudev (European Journal of Dentistry, 2025)
To investigate the dislodgement resistance of AH Plus and CeraSeal sealers to root dentin conditioned with Dual Rinse 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP) (DR HEDP) or Triton and to correlate their effects on the organic and inorganic content of the root dentin treated with test irrigants.Sixty single-rooted extracted human teeth were divided into two groups and irrigated with DR HEDP or Triton. These samples were further divided into two subgroups to study the dislodgement resistance of AH Plus and CeraSeal sealers. Middle third root sections were obtained, filled with AH Plus or CeraSeal sealers, and were subject to push-out bond strength (POBS) analysis. Fourier-transform infrared (FTIR) spectra of root dentin treated with test irrigants were obtained to analyze the changes in organic and inorganic content.POBS and FTIR values were normally distributed and hence the average values were contrasted among the groups using one-way analysis of variance with the post hoc Tukey's honest significant difference test.DR HEDP exhibited the highest dislodgement resistance of both CeraSeal and AH Plus sealers to root dentin in contrast to Triton and saline. Saline demonstrated the lowest dislodgement resistance with both the sealers tested. Posttreatment amide III: phosphate ratio was increased with saline compared with DR HEDP or Triton. Posttreatment carbonate: phosphate ratio was increased with DR HEDP compared with Triton or saline.Root conditioning with DR HEDP prior to sealer placement was beneficial for the adhesion of both AH Plus and CeraSeal sealers.
Keywords: adhesion; Dual Rinse HEDP; irrigation; root canal sealers; Triton